Developing SWOT/ TOWS Strategic Matrix for E-Banking in Lebanon - Jibai, Bilal; Alaaraj, Hassan; Issa, Abbas (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2018)
The banking sector of Lebanon has witnessed a significant shift in its performance and services provided over the past years in line with the global transformation in information technology. The diffusion of internet in most of financial sectors has driven the banking sector to adapt new technologies and deliver its services electronically through E-banking. This paper highlights the current state of e-banking in Lebanon and analyzes the secondary data of previous literature to develop a SWOT/ TOWS strategic matrix. Policy makers, Bankers and online banking users can benefit from this study for better understanding and application of e-banking in Lebanon. Future studies can extend the literature and show more evident and updated data in terms of strength, weakness, opportunities and threats facing the e-banking sector in Lebanon or compare it to other countries strategies.Â